Impact of Clinical Pharmacist-Provided Education onMedication Adherence Behaviourin ESRD Patients on Haemodialysis: Role of clinical pharmacist on medication adherence - Belagodu Sridhar Sathvik,; Gurumurthy Parthasarathi,; Moda Gopalakrishna Narahari,; Konana Chennabasappa Gurudev, (Iranian Journal of Pharmaceutical Sciences, 2009)
The aim of this research is to assess the impact of clinical pharmacist-provided education on medication adherence in haemodialysis patients. Ninety haemodialysispatients were randomized in to two groups. Brief medication questionnaire (BMQ),a tool for screening adherence was administered to both groups at the baseline toassess adherence to antihypertensives, vitamin D analogues, phosphate binders and folic acid in haemodialysis patients. The intervention group received education regarding their medications by a clinical pharmacist over seven weeks. The control group received standard care. At the end of eight weeks, BMQ was once again administered to patients of both groups. At the baseline, there was no significant difference in the mean BMQ regimen, belief, recall and the medication accesss creen scores of the control and intervention groups. At the end of the eighth week,there was a significant drop (p<0.05) in the mean scores of regimen, belief and recall screens of BMQ in the intervention group, indicating an improved level of medication adherence. For the control group, there was no significant drop in the mean BMQ screen scores. The reported level of non-adherence was the highest for phosphate binders. We conclude that clinical pharmacist-provided education was effective in improving adherence behaviour of haemodialysis patients.